Political Boycotts of the Olympic Games : A Comparative Analysis of Sochi 2014 and Beijing 2022 - Magomed-Saidov, Artem (2025)
This thesis compares the political boycotts of the 2014 Sochi Olympics and the 2022 Beijing Olympics. It examines why different states chose to boycott or not, how these decisions were communicated, and what political goals they were meant to achieve. The thesis also studies how these boycotts affected relations between the participating countries, especially with Russia and China, and how international organisations reacted. By analysing both cases, the thesis shows that political boycotts of sports events are used as symbolic tools rather than practical measures. They aim to send political messages but rarely change the behaviour of the target states. The comparison also helps to understand how global politics, human rights concerns, and international image influence decisions around major sports events.